2013
DOI: 10.4238/2013.december.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of neonatal dorsal root ganglion-derived neural stem cells into oligodendrocytes after intrathecal transplantation into a cauda equina lesion model

Abstract: ABSTRACT. Cauda equina syndrome (CES) is characterized by varying patterns of low back pain, sciatica, lower extremity sensorimotor loss, and bowel and bladder dysfunction. The prognosis for complete recovery of CES is dependent on not only the time before surgical intervention with decompression but also the severity of the nerve damage. Delayed or severe nerve compression impairs the capability of nerve regeneration. Transplantation of neural stem cells (NSCs) may facilitate axon regeneration and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Accumulating evidence demonstrates that transplanted NSCs successfully survive in the injured tissues and integrate into the host brain to achieve the functional recovery [19]. Moreover, the pluripotency of DRG has been reported by several research groups, including our group [15,20,21]. The sensory branch in the cauda equina is composed of the central processes of DRG neurons.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Accumulating evidence demonstrates that transplanted NSCs successfully survive in the injured tissues and integrate into the host brain to achieve the functional recovery [19]. Moreover, the pluripotency of DRG has been reported by several research groups, including our group [15,20,21]. The sensory branch in the cauda equina is composed of the central processes of DRG neurons.…”
Section: Discussionmentioning
confidence: 90%
“…Because the cauda equina is different from the spinal cord, it is impossible to transplant the neural stem cells into the solid tissues. Our previous study showed that GFP-NSCs survived in the cerebrospinal fluid around the damaged cauda equina after intrathecal transplantation, but the surviving time was very short, i.e., only one week [15]. Based on the previous study, hydrogels were used to localize neural stem cells to the injured cauda equina to promote the axon regeneration and remyelination of damaged cauda equina, eventually achieving the goal of neuron preservation and functional repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pasteur pipettes were used to gently blow the neurospheres, place them at 37°C for 20 min, then centrifugation, and the supernatant was discarded. The preparation was suspended in a small amount of medium, gently beaten and mixed, counted, then laid in a 6-well plate, and each hole had about 200-300 neurospheres (13). After 3 generations of subcloning, the NSCs were derived from the neurospheres.…”
Section: Culture Of Drg-nscsmentioning
confidence: 99%